Structural Interdicts for Socio-economic Rights: What the Kenyan Jurisprudence Has Missed - Law Clinic, Strathmore (Strathmore Law Review, 2019)
The enforcement of socio-economic rights is unique as it necessitates positive action in policy-making and bears budgetary implications. Consequently, to prevent such enforcement from exceeding the scope established by the doctrine of ‘separation of powers’, because policy-making and budgetary allocation are under the executive and legislature respectively, the Kenyan Court of Appeal was hesitant to apply structural interdicts in the case of Kenya Airports Authority v Mitu-Bell Welfare Society & 2 others. This decision has outlawed structural interdicts from the Kenyan jurisprudential landscape and has failed to give a viable alternative judicial approach that should guide subsequent courts in enforcing socio-economic rights. This study looks into the origin and models of structural interdicts so as to analyse and critique this Court of Appeal’s decision by showing how the Court could have applied structural interdicts in the enforcement of socio-economic rights without impinging on the doctrine of separation of powers. This will be achieved through the use of literature review.